PENGGUNAAN MODEL TEAM ASSISTED INDIVIDUALIZATION (TAI) DENGAN MEDIA VIDEO UNTUK PENINGKATAN HASIL BELAJAR IPS SISWA KELAS IV SEKOLAH DASAR - ANAJAH, HIKMAH (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Using of Team Assisted Individualization (TAI) Models with Video Media to Improve Leraning Outcomes Social Science In The Fourth Grade Elementary School. The purpose of this research to improve the learning outcomes social science in fourth grade elementary school. This study is a collaborative action research conducted in three cycles, in cycles include the planning, acting, observation, and reflection. The subject were fourth grade elementary school. Data source of this study are students, teachers, and observers. Data was collected was with test and non-test techniques. The validity of the data using triangulation technique and triangulation of data sources. Conclusi of this study is the using of TAI model with video media can be improve learning outcomes in social science fourth grade student elementary school.Keywords: TAI model, video media, social science outcomes. Abstrak: Penggunaan Model Team Assisted Individualization (TAI) dengan Media Video untuk Peningkatan Hasil Belajar IPS Siswa Kelas IV Sekolah Dasar. Penelitian ini bertujuan untuk meningkatkan hasil belajar IPS siswa kelas IV SD. Penelitian ini adalah penelitian tindakan kelas kolaboratif yang dilaksanakan dalam tiga siklus, masing-masing siklus mencakup tahap perencanaan, pelaksanaan, observasi, dan refleksi. Sumber penelitian ini adalah siswa kelas IV SD. Sumber data penelitian ini adalah siswa, guru, dan observer. Teknik pengumpulan data dilakukan dengan teknik tes dan non tes. Validitas data menggunakan triangulasi teknik dan triangulasi sumber data. Simpulan penelitian ini adalah penggunaan model TAI dapat meningkatkan hasil belajar IPS siswa kelas IV SD.Kata kunci: model TAI, media video, hasil belajar IPS.